Optical fibre long period grating gas sensor modified with metal organic framework thin films - Hromadka, Jiri; Tokay, Begum; Korposh, Sergiy; James, Stephen (Elsevier, 2015)
An optical fibre long period grating (LPG) modified with a thin film of ZIF-8, zeolitic immidazol framework material, a subgroup of metal organic framework (MOF) family, was employed for the detection of organic vapours. ZIF-8 film was deposited onto the surface of the LPG using in-situ crystallization technique by mixing freshly prepared 12.5 mM zinc nitrate hexahydrate and 25 mM of 2-metyl-imidazole solutions in methanol. ZIF-8 film was characterized by scanning electron microscope (SEM) images, thickness and refractive index (RI) has been calculated with use of ellipsometer for films containing of 1,2,3,5 and 10 growth cycles. The crystallinity of the film was confirmed by x-ray diffraction pattern (XRD). The LPG sensor was designed to operate at the phase matching turning point to provide the highest sensitivity. The sensing mechanism is based on the measurement of the RI change induced by the penetration of the chemical molecules into the ZIF-8 pores. LPG modified with 2 and 5 growth cycles of ZIF-8 responded to exposure to methanol, ethanol, 2-propanol and acetone. The sensitivity of the measurements to humidity as an interfering parameter was also investigated.